Thermal equilibrium safety assessment of storage and transportation for 2, 2'-Azobis(2, 4-dimethylvaleronitrile) initiator required for polymer resin in construction industries. Issue 1 (1st January 2021) - Tsai, Chia-Feng; Wen, I-Jyh
Abstract: Polymer materials, such as polymer concrete, have long played an important role in the construction industry. A cement and water-free building binder is formed by polymerizing monomers and initiators, and this process has many advantages in terms of green concrete. Compared with polymerized monomers, the initiator needs to provide the energy required to lower the polymerization threshold, and these energetic properties lead to thermal hazards. Azo compounds are one type of energetic polymerization initiator that can cause serious fire and explosion hazards. If the safety measures for phase changes in reactions (for example, in an endothermic process or a cooling system) fail, serious fires and explosions will occur. To ensure the thermal safety of an overall reaction process, 2, 2ʹ-azobis (2, 4-dimethylvaleronitrile) (ABVN), which is usually used for polymerization, was selected in this study. The exothermic mode and basic thermal hazard of ABVN were analyzed using a C80 microcalorimeter, which has low interference from the external temperature. The results of this study reveal the reaction form of ABVN through kinetic analysis. The thermal hazard of ABVN during actual thermal decomposition was analyzed using a thermal equilibrium calculation, and the storage and transport hazard characteristics of 25.0 kg and 50.0 kg ABVN packages were also determined. The results show that ABVN exhibits obvious thermal hazard characteristics when the temperature is higher than 35 °C (SADT<35 °C). Therefore, with the TMR value as the basis for design safety, the TCL is recommended to avoid high-temperature environments.